Echocardiographic left ventricular size in the selection of surgical treatment in patients with tetralogy of Fallot - Özkutlu, Süheyla; Saraçlar, Muhsin; Özme, Şencan; Yurdakul, Yurdakul (The Turkish Journal of Pediatrics, 1987)
Fifty-six cases with tetralogy of Fallot are presented. The left ventricular dimensions of the subjects were measured by M-mode echocardiography before undergoing surgical treatment. After surgery the patients were divided into two groups. Group I consisted of 43 patients who had survived. Group II consisted of 13 patients who had died. The age ranges were between three and sixteen years in both groups. The mean values of the left ventricular end-diastolic dimensions (LVEDD) were 71 ± 2.15 percent (with a range between 50 and 109) of normal in Group I, and 63 ± 2.91 percent (with a range between 51 and 96) of normal in Group II (t = 3.57, p < 0.05). The relationship between the LVEDD and the body weight of the patients in Group I showed an r value of 0.53 (p < 0.01) which means that as the body weight increases the left ventricular size becomes more enlarged. However, no such relationship was present in Group II (r = 0.339, p > 0.05). It may be presumed that with the increase in body weight, the left ventricular size of the cases in this group showed much slower improvement. According to our data, 35 percent of our cases (Group II) whose LVEDD fell below 66 percent (upper limit of the mean percent of the exitus line) of normal died, while 70 percent died because of left-sided heart failure. It is concluded, therefore, that for successful primary repair, a left ventricular dimension above a certain level is necessary, and we suggest that the limit line as an indication for corrective surgery or shunt operation be 66 percent of the normal values.